Effect Of Similar And Dissimilar Aluminum Alloy Tailor Welded Blank To Twist Springback - Nasir, Iskandar Mirza Mohd (Universiti Sains Malaysia, 2021)
In an automotive industry, aluminium alloys-based tailor welded blanks are demanding materials for various components due to its low density and good mechanical properties, especially when it is offered weight reduction in the automotive industry However, stamped metal mostly experiences springback defects, which would result in components that do not conform to the required product tolerances and twist springback is among the most difficult to predict. Past studies on the measurement and prediction of twist springback have mostly focused on virgin material, and studies on similar and dissimilar grade aluminium-based tailor welded blanks are still lacking and demanding. In this study, the effect of moment applied and material type on several types of aluminium based tailor welded blanks on twist springback will be studied. The twist forming process was modelled in a commercial FEA software, ANSYS Workbench, using a static structural analysis procedure. The results have shown that dissimilar aluminium would decrease the twist springback, while a similar aluminium increases the twist springback. In conclusion, all the parameters chosen had significant effects on the springback behaviour. The comparison between similar and dissimilar aluminium have shown major difference on the twist angle after loading. This difference could be attributed to the strain hardening effect in the production of the similar and dissimilar aluminium profiles.